Dampak Ekonomi Dhuafa Terhadap Mutu Pendidikan (Interactive Model Analysis) - Muthiah Shafana Adiyanti; Moh Supendi (Jurnal Pendidikan Ekonomi (JUPE), 2023)
This study aims to describe how the economic impact of the poor has on the quality of education, the implementation of the financing system in the system of dhuafa schools, as well as the supporting and inhibiting factors. The object of research is the MEKARSARI 01 Middle School. The sampling technique uses purposive sampling with the subject of the principal, teacher and parents of students. Data analysis techniques using Interactive Model Analysis. Methods of data collection using observation and interviews. Checking the validity of the data using data and source triangulation techniques. The results of the research indicate that elements of the government (especially the scope of education) and the organizations concerned provide assistance in the form of surplus funds so that the smooth running of the educational process can be maintained. The researcher hopes that further research will try to make or formulate an efficient practicum model for the poor.